Payung Hukum Penetapan Awal Bulan Qamariyah - M. Arbisora Angkat, (Advances in Humanities and Contemporary Studies, 2022)
Muslims in Indonesia frequently run into disagreements on the determination of beginning the month of Qamariyah, especially in Ramadhan, Syawal & Dzulhijjah. Muslims in Indonesia should be able to unite these different opinions. Global Islamic Calendar with hisab approach is a solution to this problem. The Global Islamic Calendar is in line with maqasid sharia in the form of religious protection (hifz ad-din). The Global Islamic Calendar is required to be supported by legal authorities through legislation. The purpose of this study is to criticize the legal protection for determination of the beginning of the month of Qamariyah by using a descriptive-qualitative approach with library research method.